2009
DOI: 10.1111/j.1365-3059.2008.01960.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification, pathogenicity and distribution of Penicillium spp. isolated from garlic in two regions in Argentina

Abstract: A total of 147 samples of garlic ( Allium sativum ) bulbs affected by blue mould were obtained from a variety of agroclimatic districts between December 1999 and February 2000. Penicillium species were identified using both morphological and chemotaxonomic characteristics. Penicillium allii was the predominant species isolated (81·8%) in this survey and the only species proven to be pathogenic on garlic. Other species were isolated much less frequently: P. chrysogenum (13·7%), P. brevicompactum (2·8%), P. phoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…The P. dipodomyicola species that was identified in this study has also been reported in food [28]. The A. flavipes and P. allii species are usually found to be associated with cereal grains [29][31]. To the best of our knowledge, we are the first to report the presence of this species in a stool sample from an obese individual using a culture-dependent method.…”
Section: Discussionsupporting
confidence: 58%
“…The P. dipodomyicola species that was identified in this study has also been reported in food [28]. The A. flavipes and P. allii species are usually found to be associated with cereal grains [29][31]. To the best of our knowledge, we are the first to report the presence of this species in a stool sample from an obese individual using a culture-dependent method.…”
Section: Discussionsupporting
confidence: 58%
“…The strain C7B20 reported under the accession number MT122170 agreed with the description of P. allii (Frisvad and Samson 2004;Vincent and Pitt 1989). P. allii Vincent & Pitt is a synonymous denomination of "Penicillium hirsutum Dierckx" and "Penicillium corymbiferum Westling" as used in earlier publications (Cavagnaro et al 2005;Valdez et al 2009;Dugan et al 2007, Dugan et al 2011). This fungus differs from P. hirsutum by fewer and more lightly coloured exudates droplets and from Penicillium crustosum by not becoming crustose on MEA.…”
Section: Discussionsupporting
confidence: 69%
“…This spice, especially in some countries, due to their gastronomic traditions, is used daily in the kitchen, and it is, therefore, essential to guarantee the daily offer on the market. However, garlic harvesting is mostly annual, and therefore, an effective garlic storage system becomes inevitable to ensure regular supplies to consumers with high quality products, free from fungal decay ( Valdez et al., 2009 ; Palmero et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Losses are associated mainly with physiological disorders and pests. Among the most important pathogens are fungi, including Aspergillus niger , A. ochraceus , Botrytis alli , Fusarium oxysporum , F. proliferatum , Penicillium purpurogenum , Rhizopus stolonifer and Stemphylium botryosum ( Valdez et al., 2009 ; Palmero et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%